Timing and trajectory of BCR::ABL1-driven chronic myeloid leukaemia - Aleksandra E. Kamizela; Daniel Leongamornlert; Nicholas Williams; Xin Wang; Kudzai Nyamondo; Kevin Dawson; Michael Spencer Chapman; Jing Guo; Joe Lee; Karim Mane; Kate Milne; Anthony R. Green; et al. (Nature, 2025)
Abstract Mutation of some genes drives uncontrolled cell proliferation and cancer. The Philadelphia chromosome in chronic myeloid leukaemia (CML) provided the very first such genetic link to cancer1,2. However, little is known about the trajectory to CML, the rate of BCR::ABL1 clonal expansion and how this affects disease. Using whole-genome sequencing of 1,013 haematopoietic colonies from nine patients with CML aged 22 to 81 years, we reconstruct phylogenetic trees of haematopoiesis. Intronic breaks in BCR and ABL1 were not always observed, and out-of-frame exonic breakpoints in BCR, requiring exon skipping to derive BCR::ABL1, were also noted. Apart from ASXL1 and RUNX1 mutations, extra myeloid gene mutations were mostly present in wild-type cells. We inferred explosive growth attributed to BCR::ABL1 commencing 3–14 years (confidence interval 2–16 years) before diagnosis, with annual growth rates exceeding 70,000% per year. Mutation accumulation was higher in BCR::ABL1 cells with shorter telomere lengths, reflecting their excessive cell divisions. Clonal expansion rates inversely correlated with the time to diagnosis. BCR::ABL1 in the general population mirrored CML incidence, and advanced and/or blast phase CML was characterized by subsequent genomic evolution. These data highlight the oncogenic potency of BCR::ABL1 fusion and contrast with the slow and sequential clonal trajectories of most cancers.